Isolation and identification of Aeromonas spp. from Clinical and Environmental sources and study It’s Sensitive for Antibiotic - Salman, Safaa M.; Hussien, Azhar N. (Al-Qadisiyah Journal of Pure Science, 2017)
Total of 259 samples fromvariant clinical source for patients of AL-Diwanyia’s hospitals and environmental source (water) were collected from the date 10/11/2012 â€“ 10/3/2013 ,Biochemical and morphological characterization tests besides use of API 20 Eand Vitek System showed that seventeen isolates wereidentified as Aeromonas spp.These Isolates characterized as : 8 Isolates belong to Aeromonashydrophila , 4 Isolates belong to Aeromonassobria , 4 Isolates belong toAeromonascaviae and one isolate belong toAeromonassalmonicida .Antibiotic susceptibility tests of all the isolates towards ten antibiotics agents were carried out and results showed that 76.47 % were resistant to PenicillinG , 82.35 % resistant to Clindamycin ana 100 % sensitive for Imipenem,Meropenem , Ciprofloxacinand Amikacin , 17.64 % showed resistant to Chloramphenicol . The Isolates showed different sensitive for Gentamicin Ùˆ Cefotaxime Ùˆ Ceftriaxone ( 88.23 % , 70.58 % , 76.47 % ) .